Vliv chronického podávání etanolu na průbĕh experimentální adriamycinové nefropatie - Tesar, V; Zima, T; Poledne, R; Stejskalová, A; Stípek, S; Tĕmínová, J (Casopis lekaru ceskych, 1994)
BACKGROUND: Alcoholic liver disease may be in humans frequently complicated by mesangial proliferation and sclerosis. The influence of chronic ethanol administration on experimental nephrotic syndrome has not been, however, studied yet. METHODS AND RESULTS: Experimental nephrotic syndrome was induced in rats by the i.v. administration of adriamycin in ethanol fed rats and in rats given common laboratory chow. Chronic administration of ethanol was in nephrotic rats accompanied by the exaggerated lipolysis (free fatty acids were in control nephrotic rats lower than in nephrotic ethylic rats 6 weeks after adriamycin administration: 914.8 + 96.8 mumol/l vs. 1186.3 + 178.7 mumol/l, p < 0.01) and increased proteocatabolism; the development of nephrotic syndrome was ameliorated, or at least delayed, however, in ethylic rats (control nephrotic rats had higher proteinuria than nephrotic ethylic rats 3 weeks after adriamycin administration: 5.79 + 3.15 vs. 0.55 + 0.34 g protein/mmol creatinine, p < 0.01). In autopsy, diffuse global glomerulosclerosis was found in control nephrotic rats with only mild focal and segmental changes in nephrotic ethylic rats. CONCLUSIONS: Chronic ethanol administration ameliorated and/or delays the development of nephrotic syndrome in adriamycin nephropathy in rats. Mechanism of this effect of chronic ethanol feeding remains to be elucidated. Metabolic, immunosuppressive and renal haemodynamic effects of ethanol should be taken into consideration.
Keywords: potkani Wistar; Rats; doxorubicin; Nephrotic Syndrome; nefrotický syndrom; Animals; ethanol; Doxorubicin; krysa rodu Rattus; Ethanol; mužské pohlaví; Male; Rats, Wistar; zvířata